Black Youth and African-Centered Interventions: A Systematic Review. (January 2022) - Lateef, Husain; Amoako, Emmanuel O.; Nartey, Portia; Tan, Jia; Joe, Sean
Purpose: This review discusses the effectiveness of African-centered interventions (ACIs) with Black youth. Methods: The authors conducted a comprehensive search of ACIs using electronic bibliographic databases to identify studies completed in the United States and reported in peer-reviewed journals. A total of 10 studies were identified that met the full inclusion criteria of the review. Results: Collectively, we found that ACIs are associated with positive outcomes in Black youths' academic achievement, self-concept, cultural identity, and behaviors. However, there was a noteworthy amount of heterogeneity in studies' methodological rigor. Discussion: The small number of studies identified support the need for additional research with high standards of methodological rigor to further determine the effectiveness of using ACIs over universal interventions with Black youth.